1987
DOI: 10.1085/jgp.90.2.197
|View full text |Cite
|
Sign up to set email alerts
|

The control of Na+/H+ exchange by molecular oxygen in trout erythrocytes. A possible role of hemoglobin as a transducer.

Abstract: A B S T R A C T It has previously been shown that addition of catecholamines to a suspension of trout erythrocytes induces an enlargement of the cells owing to an uptake of NaC! mediated by a cAMP-dependent, amiloride-sensitive Na+/ H + exchange. In this article, we show that the change in cell volume induced by catecholamines is much greater when the erythrocytes are incubated in N2 than when they are in 02. This difference is explained by an inhibition of the cAMP-dependent Na+/H + exchange by 02. The inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 22 publications
4
69
0
Order By: Relevance
“…Similar mechanism is discovered in adaptation of fishes to lack of oxygen in the water. It is shown that in condition of hypoxia and rise of outside temperature, increase of Na ions level accompanied by water absorption occurs in erythrocytes [52][53][54][55]. Consequently, the volume of erythrocytes increases resulting in increase of their oxygen bearing volume due to additional capture of oxygen [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar mechanism is discovered in adaptation of fishes to lack of oxygen in the water. It is shown that in condition of hypoxia and rise of outside temperature, increase of Na ions level accompanied by water absorption occurs in erythrocytes [52][53][54][55]. Consequently, the volume of erythrocytes increases resulting in increase of their oxygen bearing volume due to additional capture of oxygen [56].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the volume of erythrocytes increases resulting in increase of their oxygen bearing volume due to additional capture of oxygen [56]. It is believed that increase in the content of Na ions in erythrocytes in condition of adapting of fishes to lack of oxygen is connected with amplification of activity of Na + /H + transporter [52,53]. Perhaps, this ionic pump also participates in increasing concentration of Na ions in oocytes during their transition from maturity Stage IV to V. To prove this, additional studies of oocytes in vitro are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…(A) is the NaVH^ exchanger pNHE, which, as indicated by the equal sign can also exchange Li* for H+. (B) is the protein respon sible for the DMA insensitive Na+/Li+ exchange activity, isopr = isoproterenol, (3 = (3 adrenergic receptor, PKA = protein kinase A, proterenol and inhibited by either DMA or 0 2 (Borggreven et aL, 1995) and therefore can be attributed to the trout erythrocyte Na+/H+ exchanger, ^NHE (Motais, Garcia-Romeu & Borgese, 1987;Motais et ah, 1990;Borgese et al, 1992;Guizouarn et al, 1993). The Na+/ Li+ exchange activity in these membranes, however, was not influenced by either of these components (Borggreven et aL, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of catecholamines to a trout red blood cell suspension promotes a large increase in cell volume (Baroin, Garcia-Romeu, Lamarre & Motais, 1984a;Bourne & Cossins, 1982;Nikinmaa, 1982;Borgese, Garcia-Romeu & Motais, 1987 a) as a result of an accumulation of sodium and chloride, part of the entering sodium then being rapidly exchanged for potassium via the sodium-potassium pump (Baroin et al 1984a).…”
Section: Introductionmentioning
confidence: 99%
“…when a trout is submitted to a deep and rapidly developed hypoxia, a welldefined metabolic acidosis occurs which is due to the ,J-adrenergic-controlled release of H+ from crythrocytes via the Na+-H+ exchanger , and simultaneously the haemoglobin oxygen affinity is increased (Tetens & Lykkeboe, 1985; Claireaux, and (3) the activity of the Na+-H+ exchanger is controlled by the partial pressure of oxygen in the saline. This control is triggered by the binding of molecular oxygen to haeme which, via the modification in the quaternary structure of the haemoglobin molecule, could affect the exchanges (Motais, Garcia-Romeu & Borgese, 1987). This control of Na+-H+ exchanges by the partial pressure of oxygen in the blood appears as a regulatory loop in a process serving to increase the carrying capacity of erythrocytes for oxygen in deep hypoxia.…”
Section: Introductionmentioning
confidence: 99%